(untitled) (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study analyzes the structural relationships between knowledge management, innovation management, and work motivation on teacher performance through work discipline as a key mediating variable. The research was conducted at MTS Negeri Sekota Sungai Penuh, Jambi Province, with a sample of 142 teachers. Data were collected using a quantitative survey and analyzed using the Structural Equation Model (SEM) approach. The results show that knowledge management (β = 0.31, p < 0.01), innovation management (β = 0.28, p < 0.05), and work motivation (β = 0.35, p < 0.01) significantly affect work discipline. Furthermore, work discipline (β = 0.42, p < 0.001) has a significant mediating effect on teacher performance, indicating that discipline acts as a crucial pathway linking management and motivational factors to performance outcomes. The model confirms that strengthening teachers’ discipline can enhance the positive impact of knowledge, innovation, and motivation on overall performance.